Reduction in pediatric growth hormone deficiency and increase in central precocious puberty diagnoses during COVID 19 pandemics - Martina Peinkhofer; Benedetta Bossini; Arturo Penco; Manuela Giangreco; Maria Chiara Pellegrin; Viviana Vidonis; Giada Vittori; Nicoletta Grassi; Elena Faleschini; Egidio Barbi; Gianluca Tornese (BMC, 2022)
Abstract Background While several studies have been published so far on the effect of COVID-19 pandemic on health care for non-COVID-19 diseases, to date no study evaluated the impact of the COVID-19 pandemic on the entire field of pediatric endocrinology. This study aimed to evaluate differences in pediatric endocrine stimulation tests after the advent of COVID-19 pandemics. Methods Retrospective study with data collection for pediatric endocrine stimulation tests performed in 2019 and 2020 in a tertiary center. Results Overall, 251 tests were performed on 190 patients in 2020, compared to 278 tests on 206 patients in 2019 (− 10% tests; − 8% children evaluated). A significant reduction was found in tests to diagnose growth hormone deficiency (GHD) (− 35%), while LHRH tests increased (+ 22%). A reduction of 30% in GHD diagnosis was observed. Central precocious puberty (CPP) diagnosis increased by 38% compared to 2019, mainly in females. Conclusion This study found a significant reduction of tests investigating GHD during COVID-19 pandemics. It also showed a clinically meaningful increase in cases of CPP in girls. These results suggest the need for families and pediatricians to monitor children's growth during isolation and enlighten new perspectives towards conditions associated with lockdown restrictions as increased screen time, social isolation, and children's anxiety as possible triggers of CPP.